Application de la plasticité Associée et Non Associée pour les tôles inoxydables ferritiques - Chahaoui Oualid; Boulahrouz Salim; Ledmi Makhlouf (University Of Eloued جامعة الوادي, 2020)
The characterization of the drawability of rolled sheets is based on the determination of several features, which serve as a tool of mastering and understanding the behavior of those rolled sheets destined to drawing operations. The objective of this work is to compare the thresholds functions for the plastic behavior of rolled sheets through quadratic criteria Hill48 of plasticity in case of simple uniaxial stress on the metal’s plan for the mechanic values: a) Coefficient of anisotropy of Lankford b) The yield stresses
Intervention
Keywords: mechanical modelling; texture; Hill's criterio; associate Flow Rule; Non Assocaite Flow Rule